Welfare and growth impacts of innovation policies in a small, open economy. An applied general equilibrium analysis - Brita Bye; Taran Fæhn; Tom-Reiel Heggedal (Statistics Norway, Research Department, 2007)
We explore how innovation incentives in a small, open economy should be designed in order to achieve the highest welfare and growth, by means of a computable general equilibrium model with R&D-driven endogenous technological change embodied in varieties of capital. We study policy alternatives targeted towards R&D, capital varieties formation, and domestic investments in capital varieties. Subsidising domestic investments, thereby excluding stimuli to world market deliveries, generates less R&D, capital formation, economic growth, and welfare, than do the other alternatives, reflecting that the domestic market for capital varieties is limited. Directing support to R&D rather than to capital formation generates stronger economic growth, a higher number of patents and capital varieties, and a higher share of R&D in total production. However, it costs in terms of lower production within each firm, where presence of sunk patent costs and mark-ups result in efficiency losses. The welfare result is, thus, slightly lower.
Keywords: C68; E62; H32; O38; O41; 330; Applied general equilibrium; Endogenous growth; Research and Development